2008
DOI: 10.1109/vetecs.2008.404
|View full text |Cite
|
Sign up to set email alerts
|

Simple Optimization Algorithm for MOS-Based Resource Assignment

Abstract: A novel algorithm is proposed to calculate a solution for cross-layer optimization (CLO) between application (APP) layer and medium access control (MAC) layer. The CLO problem is analyzed mathematically and for a related similar optimization problem an explicit solution is found. Based on this solution a deterministic iterative algorithm is deducted, which can approximate the solution of the original problem with little complexity in an upper bounded number of steps. There is an easy way to adapt the algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, they consider only the requested bandwidth per application and do not differentiate between different application quality levels. In , the authors focus on cross‐layer optimization between application layer and medium access control layer. The application parameters are given by a generic mathematical model for the Mean Opinion Score (MOS) as a metric for the perceived quality.…”
Section: Background and Related Workmentioning
confidence: 99%
“…However, they consider only the requested bandwidth per application and do not differentiate between different application quality levels. In , the authors focus on cross‐layer optimization between application layer and medium access control layer. The application parameters are given by a generic mathematical model for the Mean Opinion Score (MOS) as a metric for the perceived quality.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In , QoE metrics are used to differentiate between different services and thus, generate a one‐dimensional optimisation function for the radio resource management. This approach can be seen as a continuation of former work which used a so‐called utility function for resource management to define a scheduling order with respect to different application cases .…”
Section: Related Workmentioning
confidence: 99%
“…Despite the popularity of QoS-oriented schedulers design, the end-users -humans -have the decisive judgment about the received service quality. In literature, some pioneering authors (Khan et al, 2007;Saul, 2008;Saul and Auer, 2009;Thakolsri et al, 2009) showed that the application of a subjective-based approach may lead influence the QoE in multimedia services over communication systems are presented, along with some QoE estimation methods; Section 3 illustrates some scheduling algorithms, ranging from the simplest ones to QoS-aware approaches, followed by the introduction of QoS-QoE mapping strategies and utility-based optimization. Section 4 provides the main contribution of this survey, namely the presentation of recent research directions regarding QoEoriented wireless resources scheduling -state-of-the-art QoE-aware scheduling methods are discussed and classified based on the adjustments required, at the end-user devices, in order to implement the different scheduling strategies on wireless systems.…”
Section: Introductionmentioning
confidence: 99%